Generation Z students’ perspectives on Artificial Intelligence (AI) technology in English language learning - Mardiah, Henny; Nissa, Khairun (New Language Dimensions, 2024)
Technology is advancing rapidly in this globalization era. Modern technology such as Artificial Technology (AI) emerges as the result of digitalization and it has a favourable impact on many facets of life including in education sector. Generation Z or Gen Z, as digital natives, utilize digital technology including AI as an essential part of their daily routines. The purpose of this study is to investigate Gen Z students’ perspectives towards the use of technology particularly AI (artificial intelligence) technology in English language learning. The participants of this study were 30 students from English Education Department, class of TBI-3, fourth semester of State Islamic University of North Sumatera (UIN SU). Qualitative method was implemented in this study. To collect the data, two instruments were employed, through an interview technique and observation. The research findings revealed that 18 (60%) students agree with AI technology, 10 (33.3%) students were neutral and 2 (6.7%) students disagree with the utilization of AI technology in English language learning. AI technology seems to be more advanced in the future to assist human. Moreover, if it is integrated officially in education sector. Thus, Gen Z students should be wiser in accessing it. This study may broaden teachers’ and lecturers’ insight or horizon about current technology in English language learning.